Декілька античних графіті з Тіри - Станко, М.В. (Археологія, 2003)
У статті описано 10 давньогрецьких графіті з елліністичного горизонту Центрального розкопу Тіри. Заметка посвящена публикации древнегреческих граффити из раскопок Тирской экспедиции 70-х годов XX ст. Большинство из них найдено при расчистке улицы возле дома, открытого ранее А.И. Фурманской, в горизонте эллинистического времени. Публикуемые граффити в целом подтверждают установленные ранее выводы о доминировании в Тире бытовых граффити. Впервые выявлен культ Гефеста и подтвержден культ Зевса. This article is devoted to publication of the Ancient Greek graffiti from Tyras, which were found by Tyras archaeological expedition in 1970ics. Most of them were discovered in the process of cleaning a street near the building that had been earlier discovered by A.I, Furmanskaia in the Hellenistic layer. In the whole, the published graffiti corroborate previous conclusions regarding predominance of graffiti connected with everyday life in Tyras, Moreover, the existence of cult of Zeus in Tyras was confirmed, while the cult of Hephaestus was revealed there for the first time.